2016
DOI: 10.3389/fimmu.2016.00389
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7 Deficiency Ameliorates the Pathologies of Acute Lung Injury through Elevating KLF4

Abstract: Recent evidence showed that microRNA-7 (miR-7) played an important role in the pathologies of lung-related diseases. However, the potential role of miR-7 in acute lung injury (ALI) still remains poorly understood. Here, we assessed the effect of miR-7 deficiency on the pathology of ALI. We, first, found that the expression of miR-7 was upregulated in lung tissue in murine LPS-induced ALI model. Notably, we generated miR-7 knock down mice by using miRNA-Sponge technique and found that miR-7 deficiency could ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 63 publications
10
51
0
Order By: Relevance
“… reported that down‐regulation of miR‐451a affects the activation and proliferation of CD4 + T cells by targeting the transcription factor myelocytomatosis oncogene (Myc) in dilated cardiomyopathy (DCM) patients, which contribute to the immunopathogenesis of DCM. Our new research work also reports that miR‐7 deficiency alters the proportion and absolute number of CD4 + T cells in bronchoalveolar lavage (BAL), while it is related to ameliorated pathologies of acute lung injury . In the present study, we extend previous findings by demonstrating that miR‐126 deficiency could clearly elevate activation and proliferation, as well as IFN‐γ secretion, in CD4 + T cells, indicating that miR‐126 might be a novel negative factor in CD4 + T cell function.…”
Section: Discussionsupporting
confidence: 85%
“… reported that down‐regulation of miR‐451a affects the activation and proliferation of CD4 + T cells by targeting the transcription factor myelocytomatosis oncogene (Myc) in dilated cardiomyopathy (DCM) patients, which contribute to the immunopathogenesis of DCM. Our new research work also reports that miR‐7 deficiency alters the proportion and absolute number of CD4 + T cells in bronchoalveolar lavage (BAL), while it is related to ameliorated pathologies of acute lung injury . In the present study, we extend previous findings by demonstrating that miR‐126 deficiency could clearly elevate activation and proliferation, as well as IFN‐γ secretion, in CD4 + T cells, indicating that miR‐126 might be a novel negative factor in CD4 + T cell function.…”
Section: Discussionsupporting
confidence: 85%
“…Over the past decade, accumulative data have demonstrated that aberrant expression of miRNAs involved in the occurrence and development of ALI (Cai et al, ; Fang, Gao, Hao, & Liu, ). During ALI, the expression levels of miR‐7, miR‐582‐5p, miR‐582‐3p, miR‐450a‐3p, and miR‐29b are up‐regulated (Guo et al, ; Zhao et al, ), but the expression levels of miR‐125b, miR‐208a, miR‐133b, let‐7, miR‐34c are down‐regulated (Guo et al, ; Otsuki, Ishikawa, Hori, Goto, & Sakamoto, ). PGRN can be regulated by miRNAs in different physiological and pathological contexts (Jiao, Herl, Farese, & Gao, ; Qian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the cellular distribution of miR-7 in the tumors, in situ hybridization was performed according to our previous description 56 with some modifications. Briefly, before hybridization incubation, all solutions were prepared with diethyl pyrocarbonate-treated water.…”
Section: Methodsmentioning
confidence: 99%